In silico repurposing of FDA-approved drugs against MEK1: structural and dynamic insights into lung cancer therapeutics - Khan, Mohd Shahnawaz; Shamsi, Anas; Zuberi, Azna; Shahwan, Moyad (Frontiers in Pharmacology, 2025)
The dual specificity mitogen-activated protein kinase kinase 1 (MEK1) is a critical node in the RAS-RAF-MEK-ERK signaling pathway, frequently dysregulated in cancers due to mutations in upstream regulators. Despite the development of MEK inhibitors, challenges such as on-target toxicities and drug resistance persist that emphasize the need for novel therapeutic strategies. Drug repurposing offers a fast and cost-effective alternative by leveraging existing FDA-approved compounds with established safety profiles. This study employed computational approaches to identify repurposed MEK1 inhibitors through structure-based virtual screening of 3,500 FDA-approved drugs. The MEK1 crystal structure was subjected to molecular docking using InstaDock, followed by biological activity prediction, interaction analysis, and 500-ns molecular dynamics (MD) simulations to assess stability. Radotinib and Alectinib exhibited superior docking scores (−10.5 and −10.2 kcal/mol), outperforming the reference MEK1 inhibitor Selumetinib (−7.2 kcal/mol). MD simulations revealed stable drug complexes, with lower root mean square deviation (RMSD) and fluctuations (RMSF) than Selumetinib. Principal component analysis and free energy landscapes corroborated their conformational stability, suggesting robust binding to MEK1’s allosteric pocket. Radotinib interacted extensively with key residues, including Gly79 and Lys97 at the ATP-binding site, while Alectinib engaged critical residues such as Arg189 and His239. Their superior binding and conformational stability suggest the potential to overcome resistance and toxicity issues associated with existing MEK inhibitors. The structural and dynamic superiority of Radotinib and Alectinib over Selumetinib positions them as promising repurposed MEK1 inhibitors, potentially circumventing the clinical challenges of existing therapies. A limitation of this in silico study is the absence of experimental validation, which will be addressed in future work. Experimental validation is essential to confirm their efficacy and safety in MEK1-linked malignancies.